Malnutrition and its association with the mortality in liver cirrhosis; a prospective nutritional assessment in two referral centers in Iran. (April 2023) - Pashayee-Khamene, Fereshteh; Hajimohammadebrahim-Ketabforoush, Melika; Shahrbaf, Mohammad Amin; Saadati, Saeede; Karimi, Sara; Hatami, Behzad; Rashidkhani, Bahram; Ahmadzadeh, Saleheh; Kord-Varkaneh, Hamed; Hekmatdoost, Azita
Summary: Introduction: Liver cirrhosis is a chronic condition caused by different conditions including viral infection, alcoholism, and autoimmune disorders. Malnutrition is one of the complications of liver cirrhosis that is associated with poor outcomes. This study aimed to determine the association of malnutrition with mortality in liver cirrhosis patients. Methods: This prospective cross-sectional study was conducted on liver cirrhosis patients who were referred to two referral centers for liver disease in Tehran, Iran. Patients' information including demographics (age, gender, etiology of cirrhosis, alcohol and smoking history) in addition to triceps skinfold (TSF), mid-arm circumference (MAC), Child-Pugh score and Model for End-Stage Liver Disease (MELD) score were recorded in all patients. Patients were classified into A, B, and C categories based on the Subjective Global Assessment (SGA) questionnaire. Results: Among 121 participants (68.6%) were males and the mean age was 54.78. Viral infections were the most common etiology and 65 patients (56.2%) were in the classification A of Child-Pugh Score. TSF (P = 0.001) and MAC (P = 0.003) were significantly lower in SGA class C. The survival rate in SGA class C was significantly lower than other groups (P < 0.001; log-rank test). The risk of mortality in patients with SGA class A and B was 85% (HR value: 0.15; 95% CI: 0.02–0.87; P = 0.03) and 76% (HR value: 0.24; 95% CI: 0.06–0.83; P = 0.02) lower than those with SGA class C. Conclusion: Anthropometric and SGA measure are two easy and accessible methods for assessing malnutrition and mortality in liver cirrhosis patients.